Landscape and the city: A new vision for enhancing sustainability issues - Cialdea, Donatella; Leone, Antonio; Muscio, Vito (TeMA - Journal of Land Use, Mobility and Environment, 2022)
In recent times, there has been an increasing number of initiatives for developing green and agricultural areas connected to urban ones. This is certainly very positive, from many points of view, both social as well as environmental. This work presents a study regarding an Agricultural Park proposal. It is located in an urban context, which involves a populous district of the Bari Municipality (Apulia Region, Southern Italy). The role of Nature Based Solutions was further considered: they are inspired and supported by nature and could help to build land robustness increasing soil permeability and, as a result, decreasing the risk of hydraulic hazards. For this purpose, the Digital Terrain Model was utilised: obtained by the LIDAR survey, it was employed in order to create the hydrographic micro-network, giving us details of runoff paths. Consequently, agricultural activity, by increasing soil permeability, will contribute to reducing hazards. This methodology has allowed for the creation of different areas to be allocated to agricultural activity; this process started with the localisation of hydraulic micro-network and became part of the "new" landscape. Landscape management, through Agricultural Park creation, therefore turns into a catalyst for local development, due to its agriculture relevance and its ability to absorb anthropic pressures.